Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Keywords: Official Language Minority Community (OLMC)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

The South Shore of Montérégie-Centre : Towards a Portrait of the English-speaking Community - Assistance and Referral Centre (ARC); Richardson, Mary (2019)

Promoting Opportunities for Youth Community Partnerships : A Policy Brief - Lai, Edward; Winrow, Adrienne; Orme, Charlie (Youth for Youth Québec (Y4Y Québec), 2019)
Across Canada, youth retention and success have always been key in ensuring the continued vitality of official language minority communities (OLMCs). Within the context of Quebec, retention in particular is a constant challenge, where English-speaking youth are disproportionately apt to pursue professional opportunities outside of the province. While this option should never be condemned, it is nonetheless important to ensure that those who wish to remain have access to the resources necessary to help them thrive therein. With this in mind, and considering that youth retention is equally beneficial to the state, policymakers need to be in a position to support organizations that are working towards this objective.
Keywords: Official Language Minority Community (OLMC)

Careers in Mental Health - Assistance and Referral Centre (ARC) (2019)

Careers in Nursing - Assistance and Referral Centre (ARC) (2019)

Technical Medical Careers - Assistance and Referral Centre (ARC) (2019)

Therapy & Rehabilitation Careers - Assistance and Referral Centre (ARC) (2019)

English-speaking Blacks in Quebec : Highlights from the 2016 Census - Floch, William (Conference on Community Education and Development : Perspectives on English-speaking Blacks and Other Minorities, 2018)

Noirs d’expression anglaise au Québec : faits saillants du recensement de 2016 - Floch, William (Conférence sur le développement et l’éducation communautaires : Perspectives sur les noirs d’expression anglaise et autres minorités, 2018)

Évaluation du projet: project pilote d'aide à l'emploi en Gaspésie pour les jeunes d'expression anglase - Marrotte, Jayme (Committee for Anglophone Social Action (CASA), 2018)

Les communautés anglophones de la Gaspésie-Îles-de-la-Madeleine : Un profil régional - Committee for Anglophone Social Action (CASA) (2018)

Youth Internships in Community Media : A First Step Towards Capacity Building for Official Language Community Media in Minority Setting - Consortium of Official Language Minority Community Media (2018)
Keywords: Official Language Minority Community (OLMC)

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)

Job Posting : Events & Access Coordinator - State of the Arts III - English Language Arts Network (ELAN) (2018)

Job Posting : Project Manager - State of the Arts III - English Language Arts Network (ELAN) (2018)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)

Final Report: Emploi Quebec: Coasters Association - Gallibois-Robertson, Melanie (Coasters Association, 2017)

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

Workforce of Tomorrow Youth Skills Link Project - Buckle, Heidi (Coasters Association, 2015)
The Coasters Association implemented a fourth phase of the Youth Skills Link Project which began on May 18th, 2015, and ran until November 13th, 2015, funded by Service Canada. The YSLP entitled: “Workforce of Tomorrow” was designed to help out eight (8) youth between the ages of 15-30 throughout the Lower North Shore, to overcome employment barriers by enabling them to develop/improve on self-knowledge, employability skills, skills enhancement, through three weeks of Group Based Employability Skills training, and seventeen (17) weeks of work experience. The project was posted throughout the coast inviting youth to take part in the project based out of their respective communities/municipalities. A total of seven (7) applicants were received, interviews were carried out with each applicant and job placement was necessary before final selection. The selected youth derived from the Municipalities of C te Nord du Golfe du Saint Laurent, Gros Mecatina, Bonne Esperance, and Blanc Sablon were hired for twenty (20) weeks of training and work experience.

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Building a Career as an Artist - Macdonald, Amy; Shaughnessy, Kyra (2015)

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.

Building Youth Resiliency and Community Vitality Within Montreal’s English Language Population : The YES Experience with Youth Seeking to Improve their Work Situation - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2013)
In response to an increase in the number of clients’ experiencing mental health challenges in the course of their job search YES (through CHSSN) has commissioned this report to establish an evidence-based profile of the youth that they serve. At the present time, YES uses limited resources to offer additional support through a focus group that is designed for clients who are experiencing symptoms such as decreased motivation, anxiety, social isolation and diminished confidence in dealing with the transition process.
Keywords: Official Language Minority Community (OLMC)

Program Book - Youth Employment Services (YES) (2013)

ACCORD Sample Contract - English Language Arts Network (ELAN) (2012)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

Lower North Shore Youth Employability Forum - Fequet Griffin, Priscilla (Coasters Association, 2011)
The 2011 Lower North Shore Youth Employability Forum was coordinated to provide the youth on the Lower North Shore with a two day intensive training on employability skills and provide them a forum to discuss with our Council of Mayors and leading community organizations and institutions the labour force market on the Lower North Shore. The projected outcome of the forum was to expand youth’s awareness of the shortages in labour in certain skilled trades sectors of employment and to improve opportunities for youth living in smaller, rural communities where jobs and employment services are more difficult to find. Thus, the skills developed during the two day forum will allow youth to further develop their capacity to enter into the labour force and raise awareness around labour opportunities on the Lower North Shore.

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)